Website-Based Ethnomathematics Learning for Mathematical Problem-Solving: A Systematic Literature Review - Laila Hayati; Sri Subarinah; Sudi Prayitno; Muhammad Turmuzi; Muhammad Usman Hadi (Journal of Educational Studies, 2026)
Studies in mathematics education have increasingly explored the integration of digital technology and ethnomathematics in learning activities. Various digital platforms have been used to create more interactive and contextual mathematics learning experiences connected to students’ cultural backgrounds and everyday life. Previous studies also suggested that culturally connected digital learning may support students’ engagement, reasoning, conceptual understanding, and higher-order thinking skills. However, earlier research mainly focused on mobile learning, digital games, augmented reality, and blended learning, while website-based ethnomathematics learning, particularly in higher education contexts, has received less attention. This study reviewed previous research related to website-based ethnomathematics learning and mathematical problem-solving skills using the PRISMA 2020 framework. Literature searches were conducted mainly through ProQuest and supported by Google Scholar verification and manual searches through ScienceDirect. From 142 initially identified articles published within the last ten years, 17 studies met the inclusion criteria and were analyzed descriptively and thematically. The reviewed studies discussed digital games, augmented reality, multimodal learning, AI-assisted learning, virtual learning environments, and web-based platforms in mathematics education. Problem-solving, reasoning, visualization, creative thinking, and conceptual understanding were among the mathematical abilities most frequently discussed, while geometry topics appeared more dominant than other mathematical areas. The findings indicate that ethnomathematics-based digital learning has strong potential to support more meaningful and culturally responsive mathematics learning. Nevertheless, studies specifically focusing on website-based ethnomathematics learning for improving mathematical problem-solving skills in higher education settings remain limited.